UNIBUKU: UiTM book reselling web application / Anis ‘Aisyah Md Nazri and Mohammad Hafiz bin Ismail - Md Nazri, Anis ‘Aisyah; Ismail, Mohammad Hafiz (College of Computing, Informatics and Media, UiTM Perlis, 2023)
In recent years, global online retail activities have seen a pattern of continuously expanding, with strong growth momentum. As a result of this sort of demand, a market for second-hand products that allows for the sale and purchase of a variety of unused things has emerged. Nowadays, books are quite costly, making it difficult for everyone to get them. As a result, many are seeking other methods to receive their desired books at a lower cost, and one of the options is to buy a used book. Ideally, people have a tendency to purchase new items while discarding older ones. This is especially common among college students, resulting in the abandonment and waste of many items that are still available. Unfortunately, there are not many web applications or platforms suitable for students to sell their used or old books. The study proposes to develop a web application to sell, and purchase used books. Students who are less capable of owning a book can discover an UiTM book that the older senior resells in this web application, and it is less pricey than the new book. The Web Development Life Cycle approach was used for this web system development. Then usability testing is carried out in order to evaluate the acceptability and applicability of the UNIBUKU web application. Overall, the UNIBUKU web application met all criteria and achieved the project's goals of establishing a web application that enabled students to have a proper platform to acquire and sell their used books.